The translation process of Brazilian Portuguese-English cognate words - Borém, Sandro Almeida (2023)
The present study delimited itself to Translation Studies from the perspective of Psycholinguistics. It is part of a larger research project that carries out and disseminates experimental studies in language processing for bilinguals and multilinguals, bridging the gap between Translation Studies and Psycholinguistics. The present study aimed to investigate, from a psycholinguistic perspective, the cognitive processes involved in word recognition and lexical access in a language decision task and to determine whether repeated exposure to the same words in different languages in a translation task can lead to faster and more accurate translations. This general objective was divided into two specific objectives: 1) To evaluate the processing cost of Brazilian Portuguese-English cognate words compared to non-cognate words in a language decision task. 2) To investigate if there were repetition priming effects of cognate words in a translation task. The studies carried out by Laviosa (2014), Toassi (2016, 2020), Ferreira, Schwieter, and Gile (2015), de Groot (2011), Dijkstra et al. (2002, 2005, 2018), Basnight-Brown (2014), Hall et al. (2009), Grosjean (1982, 1989, 2010, 2019), among other authors, provided theoretical support for the present study. A quantitative experimental methodology was applied in real time, which provided information about the reaction time and accuracy of the participants when they performed a language decision task and a translation task. Both tasks were conducted using the PsyToolkit software (STOET, 2010, 2017). The corpus of this study consisted of 208 words in total: 26 cognate words written in Brazilian Portuguese (CGP), 26 cognate words written in English (CGE), 26 control words in Brazilian Portuguese (CTP), and another 26 control words in English (CTE). There were also 52 distracting words and another 52 confounding words. Two hypotheses were raised: H1 - The processing cost of cognate words is higher when compared to the cost of processing noncognate words in a language decision task and H2 – There are repetition priming effects of cognate words in the translation process. The results of the language decision task showed that English control words were processed faster and more accurately than the words in the other conditions. This result can be used to identify differences in processing times and accuracy for cognates and non-cognates. It might be that the control words in English had higher accuracy and shorter response times than the words in the other conditions because the participants' English was highly activated. Concerning the translation task, the results showed that repetition priming effects of cognate words were evident, therefore, hypothesis H2 was confirmed. The present study also suggested that low proficiency in English can affect reaction time and accuracy, and that the repetition priming effect may decrease with increasing proficiency. These findings can be used to foment translation studies and provide evidence of which strategies are most effective for bilinguals when accessing lexical items in different languages. It is proposed that bilinguals can experience competition between words in different languages and that increasing language exposure and strategies to inhibit cognates can benefit language comprehension. The results of the present study showed that accuracy in the translation task was above 95% in all conditions, indicating that using cognates in the classroom could help students improve language learning.